Unlocking Global Future with the Power of English: Community Service from English Experts to Indonesian Students in Pasuruan - Adibah Adibah (PASAI : Jurnal Pengabdian kepada Masyarakat, 2025)
Mastering the English language is crucial for unlocking global career opportunities. To encourage students to learn this international language and prepare them for an English standardized test, a virtual webinar was held, featuring a native English expert and an English educator from Indonesia. The participants were 101 university students from a private university in Pasuruan who completed a survey to evaluate the webinar. The results showed that the participants became more motivated to delve deeper into learning English and taking the standardized test, including the TOEFL ITP. They also gained a deeper understanding of the power of English, particularly in terms of its impact on their cognitive skills and the international opportunities it offers. However, the study was still in its initial stage, and several in-person training series would have had a higher impact on the participants.